PENGARUH KOMBINASI TERAPI BERMAIN PLAYDOUGH DAN ORIGAMI DALAM PENINGKATAN TINGKAT KONSENTRASI PADA ANAK HIPERAKTIF DI SLBN PROF. DR. SRI SOEDEWI MASJCHUN SOFWAN, S - Afillza Mellia Putry; Sri Mulyani; Yulia Indah Permata Sari (Jurnal Multidisipliner Bharasumba, 2026)
This study aims to determine the effect of a combination of play therapy using playdough and origami on learning concentration in hyperactive children. The research used a quasi-experimental method with a pretest-posttest control group design. The sample consisted of 30 children divided into an experimental group and a control group. The instrument used was the Digit Symbol Substitution Test (DSST). The results showed that before the intervention, all respondents were in the low concentration category. After the intervention, the experimental group showed a significant improvement with the mean score increasing from 37.53 to 48.12, while the control group showed no significant change. Statistical analysis using the Wilcoxon Signed Rank Test showed a p-value of 0.006 (p < 0.05), indicating a significant effect of the combined play therapy on concentration improvement. Therefore, playdough and origami therapy can be considered effective non-pharmacological interventions.